KARAKTER AMANAH PERSPEKTIF ABDULLAH ABDUH AL-’AWADHI DALAM KITAB FIQH AL-AMANAH - Adhy, Agung Wahyu; Tamam, Abas Mansur; -, Wido Supraha (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
The moral and character crisis that befell almost all levels of society is very worrying. Among the characters that are eroded and lost is the trustworthy character. Loss of trust will cause destruction and damage. This research was written to describe the character of amanah from the perspective of Abdullah Abduh al-'Awadhi in the book Fiqh al-Amanah. This research is a type of qualitative research with library research methods. Data was collected using the documentation method and then analyzed using content analysis techniques. The data source for this research comes from primary data, namely the book of Fiqh al-Amānah and skunde data, namely other supporting books such as the book of al-Amānah wa Atsaruha fii al-Mujtama' and the book of al-Amānah wa Makanatuha Fii al-Islam. The conclusion of the research is that trust has a broad meaning, not just a deposit (wadi'ah), it is all rights that must be fulfilled and guarded. So that the scope of trust becomes many and broad. If these mandates are carried out properly, they will have an impact on individuals, social influence, economic influence and scientific influence.